Produção e comércio na vila de Taubaté (1780-1830): o perfil econômico e social das elites locais - Felipe de Moura Garrido (2016)
This work studies the economic and social profile of the elites in the village of Taubaté / SP. We will study the development of various productions and their linkages in trade networks. The study also analyzes the political and social role of the central figures of the village, the relationship they had with the city council of the village and each other through credit. This research was structured from three collections of documents: crafts and letters from Arquivo Histórico Ultramarino; censuses of Maços de População present in the Arquivo Público doEstado de São Paulo; and wills and inventories of local elites, under the custody of the Arquivo Municipal de Taubaté "Félix Guisard Filho".